Impact of ownership on the international involvement of SMEs - Fernández, Zulima; Nieto, María Jesús (Journal of International Business Studies, 2006)
This paper analyses the relationship between the internationalisation strategies of SMEs and types of ownership. Different types of ownership affect firms, and this in turn will influence the internationalisation strategy adopted. Using a sample of Spanish SMEs, our results show that internationalisation is negatively related to family ownership and positively related to corporate ownership. We have also observed that the presence of a corporate blockholder in family firms encourages internationalisation. These results support the idea that ownership type influences the decision to internationalise.